Enrichment of T-cell proliferation and memory gene signatures of CD79A/CD40 costimulatory domain potentiates CD19CAR-T cell functions - Ung, Socheatraksmey; Choochuen, Pongsakorn; Khopanlert, Wannakorn; Maneechai, Kajornkiat; Sangkhathat, Surasak; Terakura, Seitaro; Julamanee, Jakrawadee (Frontiers in Immunology, 2022)
CD19 chimeric antigen receptor (CAR) T-cells have demonstrated remarkable outcomes in B-cell malignancies. Recently, the novel CD19CAR-T cells incorporated with B-cell costimulatory molecules of CD79A/CD40 demonstrated superior antitumor activity in the B-cell lymphoma model compared with CD28 or 4-1BB. Here, we investigated the intrinsic transcriptional gene underlying the functional advantage of CD19.79A.40z CAR-T cells following CD19 antigen exposure using transcriptome analysis compared to CD28 or 4-1BB. Notably, CD19.79A.40z CAR-T cells up-regulated genes involved in T-cell activation, T-cell proliferation, and NF-κB signaling, whereas down-regulated genes were associated with T-cell exhaustion and apoptosis. Interestingly, CD19.79A.40z CAR- and CD19.BBz CAR-T cells were enriched in almost similar pathways. Furthermore, gene set enrichment analysis demonstrated the enrichment of genes, which were previously identified to correlate with T-cell proliferation, interferon signaling pathway, and naïve and memory T-cell signatures. Also, down-regulated T-cell exhaustion genes in CD79A/CD40, were compared with the T-cell costimulatory domain. The CD19.79A.40z CAR-T cells also up-regulated genes related to glycolysis and fatty acid metabolism, which are necessary to drive T-cell proliferation and differentiation compared with conventional CD19CAR-T cells. Our study provides a comprehensive insight into the understanding of gene signatures that potentiates the superior antitumor functions by CD19CAR-T cells incorporated with the CD79A/CD40 costimulatory domain.